Haemodialysis related osteomalacia: a staining method to demonstrate aluminium - Buchanan, Malcolm RC (1981)
A slight modification in tissue processing and staining technique enables a previously described method for staining aluminium to be used to demonstrate aluminium in osteomalacia associated with haemodialysis. The stain appears to be accurate in diagnosing this condition and may assist in establishing the diagnosis before severe osteomalacia develops.